Colistin Resistance in Acinetobacter baumannii: Molecular Mechanisms and Epidemiology - Katarina Novović; Branko Jovčić (MDPI AG, 2023)
Acinetobacter baumannii is recognized as a clinically significant pathogen causing a wide spectrum of nosocomial infections. Colistin was considered a last-resort antibiotic for the treatment of infections caused by multidrug-resistant A. baumannii. Since the reintroduction of colistin, a number of mechanisms of colistin resistance in A. baumannii have been reported, including complete loss of LPS by inactivation of the biosynthetic pathway, modifications of target LPS driven by the addition of phosphoethanolamine (PEtN) moieties to lipid A mediated by the chromosomal pmrCAB operon and eptA gene-encoded enzymes or plasmid-encoded mcr genes and efflux of colistin from the cell. In addition to resistance to colistin, widespread heteroresistance is another feature of A. baumannii that leads to colistin treatment failure. This review aims to present a critical assessment of relevant published (>50 experimental papers) up-to-date knowledge on the molecular mechanisms of colistin resistance in A. baumannii with a detailed review of implicated mutations and the global distribution of colistin-resistant strains.